(3GdJfRjg aj EHWGd MLL GdJTHjgs - (3HOQ GdOjf Hf LeGYI eMeO Hf EHQGgjes
(3ChdgG (B:s
(3CeG HYO aEf GdPH Yf GdOjf def Jecf efg aQV hGLH hGdQO Ydi Cgd GdHOY dCgdg CeQ dGRH eY Gfg dGjbOQ Ydi GdMed Ydi GdEYJbGO EdG GdQH GdPi HjOg JUGQja bdhH GdYHGO s
(3BNQgG (B:s
(3GdMOjK GdSGOS hGdKdGKhf MOjK dG CSJMVQ ESfGOg Edi UMGHi jbhd ai MOjK GdcQSi hEfeG ZdH Ydi cKjQ ef GdeMOKjf eLQO Gdfbd hGdGcKGQ ef GdZQGFH eY Lgdge HeG jLH Gddg JYGdi ef GdUaGJ hgh ai GdMbjbI ceG bGd HYV GdGFeI GdGbJUGQ Ydi SeGY GdMOjK Hs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B155s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds